Whole genome sequencing and comparative genomic analyses of Planococcus alpniumensis MSAK28401T, a new species isolated from Antarctic krill - Yuanyuan Wang; Lingbo Ma; Jian He; Zixuan Liu; Shaoping Weng; Lumin Wang; Jianguo He; Changjun Guo (BMC Microbiology, 2021)
Abstract Background Extremophiles have attracted much attention in the last few decades, as they possess different properties by producing certain useful metabolites. However, the secondary metabolism of the extremophiles of Antarctic krill has received little attention. Results In this study, a new bacterial strain MSAK28401T from Antarctic krill was isolated and identified. The results of analysis on phenotypic, chemotaxonomic, and genomic characteristics showed that the strain MSAK28401T belongs to the genus Planococcus. Cells of this strain were coccoid (0.89–1.05 μm) and aerobic. The majority of the fatty acid content was C15:0 anteiso (37.67 ± 0.90%) followed by C16:1 ω7c alcohol (10.37 ± 1.22%) and C16:0 iso (9.36 ± 0.71%). The calculated average nucleotide identity and DNA–DNA hybridization values between the strain MSAK28401T and type strains P. citreus DSM 20549T and P. rifietoensis M8T were lower than 91 and 70%, respectively. The strain MSAK28401T (=KCTC 43283T and MCCC 1k05448T) represented a new member of the genus Planococcus and was named P. alpniumensis sp. nov. Moreover, genes involved in the degradation of aromatic compounds (e.g., salicylate, gentisate, and quinate) were found in the genome, implying that strain MSAK28401T has an aromatic compound as its potential metabolite. This work will help us understand the genomic characteristics and potential metabolic pathway of Planococcus from Antarctic krill. Conclusions This study reported the genomic information and phenotypic characteristics of the new strain P. alpniumensis MSAK28401T isolated from Antarctic krill, and provided the genome information of Planococcus strains for further studying the function roles in aromatic compound metabolism.